(untitled) (TAMADDUN NURI JURNALI, 2025)
This article is aimed at studying the impact of an international language, which is becoming popular nowadays, on the knowledge of the English language. This article examines the positive and negative aspects of the influence of the media on the language and makes a critical assessment.